2020
DOI: 10.1186/s12864-020-07267-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and population genetic analyses of copy number variations in six domestic goat breeds and Bezoar ibexes using next-generation sequencing

Abstract: Background Copy number variations (CNVs) are a major form of genetic variations and are involved in animal domestication and genetic adaptation to local environments. We investigated CNVs in the domestic goat (Capra hircus) using Illumina short-read sequencing data, by comparing our lab data for 38 goats from three Chinese breeds (Chengdu Brown, Jintang Black, and Tibetan Cashmere) to public data for 26 individuals from three other breeds (two Moroccan and one Chinese) and 21samples from Bezoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 86 publications
3
13
0
Order By: Relevance
“…In total, we identified 164,733 CNV events (144,517 deletions and 20,216 duplications) with the average number of 1647.3 per mink. Similar results were reported in other livestock species e.g., dairy cattle (182,823 CNVs) [ 70 ], yak (98,441 CNVs) [ 39 ], Nellore cattle (195,873 CNVs) [ 71 ], and goat (208,649 CNVs) [ 26 ]. Some other studies reported a wide range of CNVs from 12 CNVs in chicken [ 72 ] to 1,747,604 CNVs in sheep [ 23 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In total, we identified 164,733 CNV events (144,517 deletions and 20,216 duplications) with the average number of 1647.3 per mink. Similar results were reported in other livestock species e.g., dairy cattle (182,823 CNVs) [ 70 ], yak (98,441 CNVs) [ 39 ], Nellore cattle (195,873 CNVs) [ 71 ], and goat (208,649 CNVs) [ 26 ]. Some other studies reported a wide range of CNVs from 12 CNVs in chicken [ 72 ] to 1,747,604 CNVs in sheep [ 23 ].…”
Section: Discussionsupporting
confidence: 85%
“…The results showed that 5378 CNVR covered around 47.3 Mb (1.9%) of the mink genome, which falls within the range of several studies reported in other species, such as pig (1.72%) [ 75 ], cattle (2.5%) [ 42 ], chicken (1%) [ 32 ], quail (1.6-1.9%) [ 76 ], horse (1.3%) [ 77 ], and buffalo (2%) [ 37 ]. The CNVR covered the genome in different ranges in other species, including cat (0.3%) [ 78 ], pig (0.9%) [ 57 ], yak (6.2%) [ 38 ], [ 78 ] goat (10.8%) [ 26 ], chicken (12.8%) [ 69 ], and cattle (13%) [ 71 ]. Several reasons might affect the quantity of CNVR detection such as the detection algorithm, population size, genetic background, the quality of applied technology, and the differences in genome size [ 73 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data that support the findings of this study have been deposited into CNGB Sequence Archive (CNSA) (Guo et al 2020) of China National GeneBank DataBase (CNGBdb) (Chen et al 2020) with accession number CNP0001896…”
Section: Data Availabilitymentioning
confidence: 73%
“…Meanwhile, some genes, such as FGF5, SGK3, IGFBP7, OXTR, ROCK1, LHX2, FGF9, PRDM6 and WNT2 were intensively selected in cashmere goats (Wang et al 2016;Li et al 2017;Zhang et al 2018). Recent studies have identified several causal genes for cashmere growth trait, including FGF5 and EDA2R (Cai et al 2020;Guo et al 2020). FGF5 is a regulator of the hair growth cycle, and the disruption of FGF5 is associated with a long hair characteristic (Wang et al 2016;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, disruption of the FGF5 gene via the CRISPR/Cas9 system in cashmere goats increased the number of SHFs and enhanced the fibre length (Wang et al 2016a(Wang et al , 2016b. Recently, the studies of Cai et al (2020) and Guo et al (2020) reported a genetic variant located at ~14 kb downstream of FGF5 on chromosome 6. Cai et al (2020) identified a 504-bp deletion by using F ST methods based on SNPs and copy number variations in 24 northern Chinese goats, including 16 goat populations.…”
Section: Introductionmentioning
confidence: 99%